PENGARUH TERAPI AKTIFITAS KELOMPOK (TAK) STIMULASI PERSEPSI SESSI 1-3 TERHADAP KEMAMPUAN MENGENDALIKAN HALUSINASI PADA PASIEN SKIZOFRENIA HEBEFRENIK - Ellina, Agusta Dian (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Schizoprenia was not a single disorder, but a group of related disorder characterized by disordered thinking and perception. One positive symptoms of schizophrenia was hallucination. Hallucination generally flange at behavior that can injury themselves, other people and environment. Destructive agresive action or hardness behavior that be done by schizophrenia patient to injury themselves or other people, most of it caused by hallucination. Design used in this study was Quasy-eksperiment two group pre test- post test design, sampel consist of 14 respondent, 7 people treatment group and 7 people control group. The independent variable was group activity therapy (TAK) perspective stimulation, while the dependent variable was the ability to cut of hallucination. Data were collected using observation. Data that obtained at the time of pre test and post test would be collected and analized using Wilcoxon Signed Rank Test with level of significance <0,05, while to knew the difference of pain level post test between treatment group and control group would be analized using Mann-Whitney Test with level of significance <0,05. The result showed that giving aromatherapy had strong influence to decrease pain level of migraine patient, with the result of statistical test had same significant level p=0,014. The result showed that there was differences of pain level post test between treatment group and control group, with the result of statistical test had same significance level p= 0,002. It can be concluded that group activity therapy (TAK) perspective stimulation could increased ability to cut of hallucination. Recommendation for the nurse and other health profession to use group activity therapy (TAK) perspective stimulation to increased ability to cut of hallucination. Futher study of group activity therapy (TAK) perspective stimulation to increased ability to cut of hallucination so hopefully assisted curing prosess.